Association between echo intensity and attenuation of skeletal muscle in young and older adults: a comparison between ultrasonography and computed tomography - Watanabe Y (Dove Medical Press, 2018)
Yuya Watanabe,1–3 Masahiro Ikenaga,4 Eiichi Yoshimura,5 Yosuke Yamada,2,6 Misaka Kimura2,3 1Faculty of Health and Sports Science, Doshisha University, Kyotanabe, Japan; 2Laboratory of Applied Health Sciences, Kyoto Prefectural University of Medicine, Kyoto, Japan; 3Department of Health and Sports, Faculty of Health and Medical Sciences, Kyoto Gakuen University, Kameoka, Japan; 4Central Research Institute for Physical Activity, Fukuoka University, Fukuoka, Japan; 5Department of Food and Health Sciences, Prefectural University of Kumamoto, Kumamoto, Japan; 6Laboratory of Healthy Longevity Research, National Institute of Health and Nutrition, National Institutes of Biomedical Innovation, Health and Nutrition, Tokyo, Japan Background: Skeletal muscle experiences both quantitative and qualitative changes with aging. Echo intensity (EI) of the skeletal muscle obtained by ultrasonography (US) has been considered to reflect muscle quality. This technique is noninvasive, easily accessible, and is relatively inexpensive than that of other imaging techniques such as computed tomography (CT). Previous studies have reported that EI is related to several physical performances. However, few studies have investigated the validity of EI against other imaging methods in case of imaging of the skeletal muscle. We compared quantitative and qualitative indices evaluated by the US and CT imaging systems to strengthen their validity.Participants and methods: A total of 40 adults participated in this study: 19 young (10 men and 9 women; their mean (±SD) age was 22.7±1.5 years) and 21 older adults (13 men and 8 women; their mean age was 70.6±4.8 years). Both thighs of each participant were evaluated using US and CT imaging systems.Results: With respect to the US indices, the young group had significantly higher muscle thickness (MT) of the front thigh (P<0.001) and lower EI (P=0.001) than that of the older group. With respect to the CT indices, the cross-sectional area (CSA) and mean CT value (Hounsfield unit [HU]) of the muscle were found to be significantly higher in the young group (P<0.001) than that of the older group, whereas the percentage of low-density muscle area (%LDMA) was found to be significantly higher in the older group (P<0.001) than that of the young group. A significant, strong, and positive correlation was observed between MT and CSA, which reflects the muscle quantity (r=0.774; P<0.001). With respect to the indices of muscle quality, we found significant and moderate correlations between EI and CT values (r=-0.502; P<0.001) and between EI and %LDMA (r=0.441; P<0.001). However, these correlations were found to be decreased in the older group [between EI and CT value (r=-0.363; P=0.018) and between EI and %LDMA (r=0.257; P=0.100)].Conclusion: Results of this study indicate that the EI is moderately associated with muscle attenuation as assessed by CT, which means that higher EI at least partly reflects intramuscular lipid infiltration. Keywords: echogenicity, ultrasound imaging, CT value, low-density muscle area, muscle composition, muscle quality